1997
DOI: 10.1073/pnas.94.25.13771
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of Fhit in cancer cells suppresses tumorigenicity

Abstract: The candidate tumor suppressor gene, FHIT, encompasses the common human chromosomal fragile site at 3p14.2, the hereditary renal cancer translocation breakpoint, and cancer cell homozygous deletions. Fhit hydrolyzes dinucleotide 5,5ٟ-P 1 ,P 3 -triphosphate in vitro and mutation of a central histidine abolishes hydrolase activity. To study Fhit function, wild-type and mutant FHIT genes were transfected into cancer cell lines that lacked endogenous Fhit. No consistent effect of exogenous Fhit on growth in cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
288
1
2

Year Published

1998
1998
2006
2006

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 326 publications
(296 citation statements)
references
References 18 publications
5
288
1
2
Order By: Relevance
“…9,11,31 In addition, the status of FHIT as a candidate tumor suppressor gene in 3p14 has been well demonstrated in endocrine lung carcinomas by immunohistochemical methods 31 and by in vivo experiments. 32 Overall, the data from the current study may support the hypothesis that FHIT functions as a tumor suppressor gene in the pathogenesis of GI PDECs.…”
Section: Discussionsupporting
confidence: 73%
“…9,11,31 In addition, the status of FHIT as a candidate tumor suppressor gene in 3p14 has been well demonstrated in endocrine lung carcinomas by immunohistochemical methods 31 and by in vivo experiments. 32 Overall, the data from the current study may support the hypothesis that FHIT functions as a tumor suppressor gene in the pathogenesis of GI PDECs.…”
Section: Discussionsupporting
confidence: 73%
“…The cloning of the fragile histidine triad(FHIT) gene at 3p14.2 in 1996 (Ohta et al, 1996) and the subsequent reports demonstrated frequent allelic deletion, aberrant FHIT transcripts in primary lung cancers (Fong et al, 1997), cell lines of small cell and nonsmall cell type (Yanagisawa et al, 1996). The evidence that FHIT suppresses tumorigenicity in cancer cells (Siprashvili et al, 1997) supports the contention that FHIT is a tumour suppressor gene. This, together with the recent observation (Sozzi et al, 1997a) that there is more FHIT allelic loss in carcinomas from smokers than from nonsmokers, strengthens the case for its involvement in the multistage development of lung cancer.…”
mentioning
confidence: 61%
“…The exact molecular mechanism or functional pathway mediating FHIT's tumor suppressor action is still not fully understood. It is known that FHIT hydrolases diadenosine nucleotides into ADP and AMP, but since this enzymatic activity does not seem to be required for its tumor-suppressor function there must be other relevant features of the protein, 12 that is regulation of apoptosis. It has been demonstrated that restoration of FHIT expression in lung and cervical cancer cell lines resulted in efficient induction of apoptosis and suppression of tumorigenicity, and that the apoptotic mechanism seems to be FADD (Fas associated via death domain) dependent, caspase-8 mediated and independent from regulation through Bcl-2 or Bcl-xl.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 FHIT is known to be inactivated in various human malignancies. [9][10][11][12][13][14][15][16][17][18][19][20] FHIT inactivation by point mutation is a rare event, [21][22][23] but significant loss or reduction of expression can be caused by other mechanisms, including loss of heterozygosity (LOH) and/or promoter hypermethylation. 24 For example, FHIT hypermethylation with consequent transcriptional inactivation has been shown in breast, lung, esophageal, cervical, prostate and bladder cancer.…”
mentioning
confidence: 99%